Daya Saing Dan Komplementaritas Perdagangan Kayu Indonesia: Kasus Kawasan Asia-Pasifik - Saraswati, Ria Indah; Harianto; Rifin, Amzul (Forum Agribisnis, 2024)
Indonesia trades ten groups of wood in the Asia-Pacific region. Many forest industry problems occur during trade. Competition and interdependence in trade are research objectives. The research secondary data source is taken from UN Comtrade 2011-2021 and analyzed using the Export Similarity Index (ESI), Revealed Comparative Advantage (RCA), Trade Complementarity Index (TCI), and Intra-Industry Trade (IIT) methods. The research results show that the wood export trade between Indonesia and competing countries competes weakly with each other in the six partner countries. Indonesia is competitive in the products SITC 245 (fuel wood (excluding wood waste) and wood charcoal), SITC 248 (wood, simply worked, and railway sleepers of wood), SITC 251 (pulp and waste paper), SITC 634 (veneers, plywood, particle board, and other wood, worked, n.e.s.), SITC 635 (wood manufactures, n.e.s.), and SITC 641 (paper and paperboard). On the other hand, Indonesia and partner countries almost complement each other as trading partners in terms of exports and imports of wood. However, the integration of Indonesian wood trade with partner countries is considered weak. Products SITC 248 (wood, simply worked, and railway sleepers of wood), SITC 251 (pulp and waste paper), SITC 641 (paper and paperboard), and SITC 642 (paper and paperboard, cut to size or shape, and articles of paper or paperboard) are several product industries that have led to intra-industry trade. Policy recommendations are to utilize resources optimally, develop the wood processing industry to produce finished wood products, and improve the quality and standards of wood products in accordance with policies in trade cooperation.